2012
DOI: 10.5761/atcs.oa.11.01684
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Evaluation of Internal Thoracic Artery Anastomosed to the Left Anterior Descending Artery with 320-Detector Row Computed Tomography and Adenosine Thallium-201 Myocardial Perfusion Scintigraphy

Abstract: Purpose: We evaluated the relationship between internal thoracic artery (ITA) stenosis anastomosed to the left anterior descending artery (LAD) and the degree of LAD stenosis using 320-detector row computed tomography (320-ADCT) and adenosine thallium-201 myocardial perfusion scintigraphy (Tl-201-MPS). Methods: We included 101 patients who underwent coronary artery bypass grafting (CABG) using ITA grafts; 320-ADCT and adenosine Tl-201-MPS were performed 2-3 months after CABG. Clinical parameters, degree of LAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The comparison of capabilities for pulmonary vasculature visualization showed that mean scores for pulmonary artery and intersegmental vein assessment by ADCT were significantly higher than those by MDCT. It has been suggested in the last few years that the latest generation ADCT system has significant advantages [4][5][6][7][8][9][10][11][12][13][14][15][16]. It enables the acquisition of all dynamic data within a 16-cm area every 2 s without helical scanning and makes it possible to obtain images of the pulmonary vessels involved in a single rotation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of capabilities for pulmonary vasculature visualization showed that mean scores for pulmonary artery and intersegmental vein assessment by ADCT were significantly higher than those by MDCT. It has been suggested in the last few years that the latest generation ADCT system has significant advantages [4][5][6][7][8][9][10][11][12][13][14][15][16]. It enables the acquisition of all dynamic data within a 16-cm area every 2 s without helical scanning and makes it possible to obtain images of the pulmonary vessels involved in a single rotation.…”
Section: Discussionmentioning
confidence: 99%
“…It enables the acquisition of all dynamic data within a 16-cm area every 2 s without helical scanning and makes it possible to obtain images of the pulmonary vessels involved in a single rotation. As for the cardiovascular region, it has been reported that ADCT can provide coronary CT angiography images of excellent quality even for patients with atrial fibrillation, because ADCT enables sufficient craniocaudal coverage in a single rotation and allows imaging of the entire coronary tree within a single beat [4,7,12,16]. In addition, electrocardiograph (ECG)gated ADCT scans, which provide ECG-gated volumetric scan data of the whole lung without any additional radiation exposure, feature excellent lung image quality [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volumetric data were reconstructed with half or segmented reconstruction. 19 All scans were performed during a single breath-hold. Isosorbide dinitrate spray 1.25 mg was provided immediately before CTA.…”
Section: Methodsmentioning
confidence: 99%
“… 22 The Tl-201 uptake was graded subjectively in three orthogonal planes (short axis, horizontal long axis, vertical long axis) divided into 17 segments on a five-point scale (4=absent uptake; 3=severely, 2=moderately, 1=mildly decreased uptake; 0=normal uptake, respectively) on the post-stress and delayed images displayed side by side by the consensus of two experienced observers (MS and HK) unaware of the clinical history and CTA findings of the patients. 19 The segmental perfusion scores during stress and rest were added together to calculate the summed stress score (SSS), the summed rest score (SRS) and the summed difference score (SDS).…”
Section: Methodsmentioning
confidence: 99%